20-Hydroxy-3-Oxolupan-28-Oic Acid, a Minor Component From Mahonia bealei (Fort.) Carr. Leaves Alleviates Lipopolysaccharide-Induced Inflammatory in Murine Macrophages - Yang, Xiaojun; Zhou, Jing; He, Yang; Lv, Lingyun; Cao, Yufeng; Hu, Weicheng (Frontiers in Bioengineering and Biotechnology, 2021)
0-Hydroxy-3-oxolupan-28-oic acid (HOA), a minor component from Mahonia bealei (Fort.) Carr. leaves, has been found to attenuate inflammatory responses. However, the underlying molecular mechanism is still unclear. In this study, we performed a comprehensive transcriptional study to investigate genetic changes. We used RNA sequencing technology to analyses the transcriptional changes in RAW264.7 cells in a control group, lipopolysaccharide (LPS)-induced group, and HOA-treated group. We identified 1313 and 388 differentially expressed genes (DEGs) in the control/LPS group and LPS/HOA group, respectively. Gene Ontology (GO) classification revealed that the DEGs were mainly enriched in a series of inflammatory and immune-related processes. The results of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses showed that the DEGs were mainly enriched in inflammatory-related pathways such as the nuclear factor-kappa B (NF-κB) signaling pathway, cytokine-cytokine receptor interaction, chemokine signaling pathway, mitogen-activated protein kinase (MAPK) pathway, and Janus kinase-signal transducer and activator of transcription proteins (JAK-STAT) signaling pathway. The results of qPCR validation revealed that dynamic changes in immune-related mRNAs such as Saa3, Bcl2l1, Mapkapk2, Ccl9, Sdc4, Ddx3x, Socs3, Prdx5, Tlr4, Lif, Il15, Tnfaip3, Tet2, Tgf-β1, and Ccl20, which were significantly upregulated in the LPS group and downregulated in the HOA group. Taken together, these results suggest that HOA may be used as a source of anti-inflammatory agents as well as a dietary complement for health promotion.